Meningkatkan Profesionalitas Mahasiswa PPG Melalui Pelatihan e-Bahan Ajar dan e-Media Pembelajaran - Dudung Ma'ruf Nuris; Muhammad Alfan (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Electronic-based teaching materials and learning media are really needed by teachers who have graduated from Teacher Professional Education to equip themselves to face the digital era. This activity aims to provide new knowledge and update knowledge related to the preparation of electronic teaching materials and learning media to prospective teachers and teachers who have graduated from Teacher Professional Education. The method used is training and mentoring with direct supervision through face-to-face activities. Participants in this activity are prospective teachers and teachers who have graduated from Teacher Professional Education in the Malang area, especially in the Kepanjen area, Malang. There were 30 participants, consisting of teachers and students of Pre-Service Teacher Professional Education at Malang State University. This activity succeeded in having a positive impact on prospective teachers and teachers who graduated from Teacher Professional Education, because after participating in the activity, prospective teachers and teachers could easily create electronic-based teaching materials and learning media.